Hypoxia‐Inducible Factor‐1 Is a Determinant of Lobular Structure and Oxygen Consumption in the Liver. (11th July 2013) - Tsukada, Kosuke; Tajima, Toshihide; Hori, Shutaro; Matsuura, Tomomi; Johnson, Randall S.; Goda, Nobuhito; Suematsu, Makoto
Abstract Objective Hypoxia‐inducible factor is a hypoxia‐responsive transcriptional factor that controls the expression of proteins contributing to homeostatic responses to hypoxia. Spatial heterogeneity of tissue oxygenation has been postulated as a determinant of structure and function of hepatic lobules, although its molecular mechanisms remain unknown. This study aimed to examine the role of HIF‐1 expressed in hepatocytes in regulation of hepatic microcirculation. Methods We have generated mice harboring a floxed HIF‐1α allele, and employed the albumin‐Cre transgenic line to inactivate the gene site‐specifically in hepatocytes. Results Intravital observation of the hepatic microcirculation revealed extension of hepatic lobules in HIF‐1α‐deficient mice. Measurement of microvascular diameter, velocity, and local oxygen tension by laser‐assisted phosphorimetry showed that the oxygen consumption in the lobules of HIF‐1α‐deficient mice was greater than that in those of control mice. Isolated hepatocytes from HIF‐1α‐deficient mice also stimulated oxygen consumptions with increased contents of mtDNA. Overexpression of HIF‐1α decreased the expression of PGC‐1α mRNA, whereas the knockdown of the HIF‐1α gene increased it, suggesting that HIF‐1 regulates cellular respiration through mitochondrial biogenesis. Conclusions Our results suggest that constitutive expression of HIF‐1α in hepatocytes acts as a determinant of hepatic lobular structure and oxygen consumption by changing mitochondrial contents.